2014
DOI: 10.1139/cjpp-2014-0113
|View full text |Cite
|
Sign up to set email alerts
|

Potential pharmacological strategies for the improved treatment of organophosphate-induced neurotoxicity

Abstract: Organophosphates (OP) are highly toxic compounds that cause cholinergic neuronal excitotoxicity and dysfunction by irreversible inhibition of acetylcholinesterase, resulting in delayed brain damage. This delayed secondary neuronal destruction, which arises primarily in the cholinergic areas of the brain that contain dense accumulations of cholinergic neurons and the majority of cholinergic projection, could be largely responsible for persistent profound neuropsychiatric and neurological impairments such as mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 279 publications
0
21
0
Order By: Relevance
“…In spite of recent advances in the therapeutic treatment of OP poisonings, they usually proceed with predominance of a heavy cholinergic crisis, and even in the case of survival of a victim, delayed pathologies are often observed: the so-called "intermediate syndrome"; OP-induced distal sensorimotor axonophaty; symptoms of vegetative changes of the circulatory system; the CNS "microorganic disorders" with unknown ethiology, and so forth [190][191][192]. Because AChE is the main target of OPs, the principles of existing therapy of acute poisoning are converged to elimination of effects of AChE inhibition by OPs, that is, administration of cholinolytics (e.g., atropin), reactivators of AChE (oximes), and anticonvulsant drugs (agonists of GABA-and antagonists of glutamate receptors); as a preventive means before the alleged poisoning, reversible AChE inhibitors can be used (e.g., pyridostigmine) [193,194]. Mechanistic studies are reduced to revealing interactions of OPs with molecular targets in nerve cells.…”
Section: Endothelium and Toxicology Of Organophosphatesmentioning
confidence: 99%
“…In spite of recent advances in the therapeutic treatment of OP poisonings, they usually proceed with predominance of a heavy cholinergic crisis, and even in the case of survival of a victim, delayed pathologies are often observed: the so-called "intermediate syndrome"; OP-induced distal sensorimotor axonophaty; symptoms of vegetative changes of the circulatory system; the CNS "microorganic disorders" with unknown ethiology, and so forth [190][191][192]. Because AChE is the main target of OPs, the principles of existing therapy of acute poisoning are converged to elimination of effects of AChE inhibition by OPs, that is, administration of cholinolytics (e.g., atropin), reactivators of AChE (oximes), and anticonvulsant drugs (agonists of GABA-and antagonists of glutamate receptors); as a preventive means before the alleged poisoning, reversible AChE inhibitors can be used (e.g., pyridostigmine) [193,194]. Mechanistic studies are reduced to revealing interactions of OPs with molecular targets in nerve cells.…”
Section: Endothelium and Toxicology Of Organophosphatesmentioning
confidence: 99%
“…Secondary neuronal toxicity during severe acute OP intoxication results in brain damage (Kaur et al 2014). We tested the zebrafish model using three groups of compounds that target key components of the pathophysiological pathways of secondary neuronal toxicity: glutamate antagonists, dual-function NMDA receptor and AChR antagonists, and anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Then, a cascade of downstream events occurs, resulting in secondary neuronal toxicity. The release of excitatory amino acids (EAAs), such as glutamate and aspartate, and the activation of the N -methyl- d -aspartate (NMDA) receptors promote intracellular Ca 2+ influx, which can activate different lipases, proteases, endonucleases, kinases or phosphatases and result in severe brain damage (Kaur et al 2014). The generation of reactive oxygen or nitrogen species may also play an important role in the development of neuroinflammation and cellular death that are found in severe acute OP intoxication (Eisenkraft et al 2013; Pena-Llopis 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A follow‐up study has shown some change towards faster dosing protocols, but the variability still exists (Connors et al , ), which may be one of the reasons why atropinization is difficult to attain in some severely poisoned patients (Kaur et al ., ; Iyer et al ., ). Recent reviews covering novel and alternative ways for treating OP poisoning (Kaur et al ., ; Iyer et al ., ) have supported the Wang et al . (2014a,b) proposal that anisodamine can be used as a safe adjunct or substitute to atropine, for cases where atropinization is difficult to achieve.…”
Section: Anisodamine As An Antidote In Op Poisoningmentioning
confidence: 99%
“…A comparison of existing atropine treatment protocols in OP poisoning has shown that the protocols are poorly evidence-based, highly variable between published sources, and most of them are too slow to achieve the desired atropinization dose in time (Eddleston et al, 2004). A follow-up study has shown some change towards faster dosing protocols, but the variability still exists (Connors et al, 2014), which may be one of the reasons why atropinization is difficult to attain in some severely poisoned patients (Kaur et al, 2014;Iyer et al, 2015). Recent reviews covering novel and alternative ways for treating OP poisoning (Kaur et al, 2014;Iyer et al, 2015) have supported the Wang et al (2014a,b) proposal that anisodamine can be used as a safe adjunct or substitute to atropine, for cases where atropinization is difficult to achieve.…”
Section: Anisodamine As An Antidote In Op Poisoningmentioning
confidence: 99%